KONSEP KOSMOLOGI MANUSIA DALAM LONTAR ANGGASTYAPRANA - I Nyoman Alit; Ni Wayan Arini (Guna Widya: Jurnal Pendidikan Hindu, 2023)
Text lontar Anggastyaprana is one of the Balinese lontar tattwa formative type of Sivaistic shades that position Siwa has the highest position and is the origin of the creation of human (Bhuwana Alit) called Sang Hyang Siwatma. This lontar describes cosmology in small scope especially regarding the process of human birth (Bhuwana Alit), the concept of its maintenance, and the concept of melting which not yet known by the public.